Pengenalan Teknik Vertikultur untuk Budidaya Sayuran di Pekarangan Rumah di Desa Gapura - Saidah, Humairo; Purwangsa, Herdi; Rohani, Rohani; Karyawan, I Dewa Made Alit; Hasyim, Hasyim; Salehuddin, Salehuddin; Negara, I Dewa Gede Jaya (Universitas Mataram, 2024)
The Sustainable Food Home Area Program (KRPL) is an activity that encourages residents to develop a small-scale food crops, animal husbandry and fisheries by utilizing their home gardens. Since community activity are restricted during Covid-19, the economy become unstable and decrease the ability to meet food needs. This activity aims to re-empower the community by introducing a verticulture technique utilizing bamboo and used bowl that are easily found in the village and supporting the KRPL program. The verticulture technique is suitable for application to vegetable plants, including mustard greens, kale, chilies, eggplants and onions. This activity was carried out in Gapura Village, Pujut District, Central Lombok Regency, West Nusa Tenggara. The method used is direct counseling and training in making verticulture media from bamboo. Through this activity, the Gapura village community has additional knowledge and stimulation in creativity to maximize the use of existing land potential to create food resilience especially vegetables and support welfare.